Flexural Fatigue-Life Assessment and Strength Prediction of Glass Fibre Reinforced Polymer Concrete Composites. (27th March 2014) - Bedi, Raman; Singh, S. P.; Chandra, Rakesh
Abstract : The paper presents the results of an investigation conducted to assess the fatigue-life and prediction of flexural fatigue strength of polymer concrete composites based on epoxy resin as binder material. Three point flexural fatigue tests were conducted on polymer concrete specimens using MTS servo controlled actuator, to obtain the fatigue lives of the composites at different stress levels. One hundred and thirty-seven specimens of size 40 × 40 × 160 mm were tested in flexural fatigue. Forty-three static flexural tests were also conducted to facilitate fatigue testing. It has been observed that the probabilistic distribution of fatigue-life of polymer concrete composite (PCC) and glass fibre reinforced polymer concrete composite (GFRPCC), at a particular stress level, approximately follows the two-parameter Weibull distribution, with statistical corelation coefficient values exceeding 0.90. The fatigue strength prediction model, representing S-N relationship, has been examined and the material coefficients have been obtained for GFRPCC containing 0.5% and 1.0% glass fibres. Design fatigue lives for GFRPCC containing different contents of glass fibres have been estimated for acceptable probabilities of failure and compared with those of PCC.